Examination on Communication and Happiness Levels of Athletes - Serhat Özdenk; Kazım Kaya (Selcuk University, 2019)
ABSTRACTAim: The aim of this study is to investigate the communication skills and happiness levels of athletes engaged in different sports branches.Material and Method: In the research, 240 amateur and professional athletes, who are active in the province of Kırşehir and volunteer, participated in the study. The questionnaire, which was formed in order to determine the characteristics of the athletes, "Communication Skills Assessment Scale (CSAS)" developed by Korkut (1996) and Happiness Scale developed by Demirci (2017) were used in data collection.Findings: When the happiness levels of the participants were examined according to gender, it was observed that the happiness levels of women were statistically significant compared to men (p gt;0.05), but there was no difference between communication skills according to gender (p gt;0.05). It was observed that professional athletes had higher levels of communication skills and happiness than amateur athletes (p lt;0.05). In the study, it was seen that the communication and happiness levels of the athletes who have 10 years or more sports experience are higher than the athletes who have less experience (p lt;0.05). It was seen that the happiness level of the participants who had 3 or more siblings were higher than the participants with 1-2 siblings (p lt;0.05). Result: As a result of the research, it was seen that female athletes' happiness levels were higher than those of male athletes, but there was no difference in communication skills of male and female participants. Professional athletes have higher communication skills and happiness levels than amateur athletes and the communication skills and happiness levels of the athletes who have 10 years or more sports experience are higher than those who have less experience. The happiness level of the participants who had 3 or more siblings were higher than the participants with 1-2 siblings.